A Framework and Blueprint for Building Capacity in Global Orthopaedic Surgical Outreach. (1st February 2023) - Shapiro, Lauren M.; Welch, Jessica M.; Chatterjee, Maya; Katarincic, Julie A.; Leversedge, Fraser J.; Dyer, George S.M.; Fufa, Duretti T.; Kozin, Scott H.; Chung, Kevin C.; Fox, Paige M.; Chang, James; Kamal, Robin N.
Abstract : Background: Nongovernmental organizations (NGOs) from high-income countries provide surgical outreach for patients in low and middle-income countries (LMICs); however, these efforts lack a coordinated measurement of their ability to build capacity. While the World Health Organization and others recommend outreach trips that aim to build the capacity of the local health-care system, no guidance exists on how to accomplish this. The objective of this paper is to establish a framework and a blueprint to guide the operations of NGOs that provide outreach to build orthopaedic surgical capacity in LMICs. Methods: We conducted a qualitative analysis of semistructured interviews with 16 orthopaedic surgeons and administrators located in 7 countries (6 LMICs) on the necessary domains for capacity-building; the analysis was guided by a literature review of capacity-building frameworks. We subsequently conducted a modified nominal group technique with a consortium of 10 U.S.-based surgeons with expertise in global surgical outreach, which was member-checked with 8 new stakeholders from 4 LMICs. Results: A framework with 7 domains for capacity-building in global surgical outreach was identified. The domains included professional development, finance, partnerships, governance, community impact, culture, and coordination. These domains were tiered in a hierarchical system to stratify the level of capacity for each domain. A blueprint was developed to guide the operations of an organization seeking to build capacity. Conclusions: The developed framework identified 7 domains to address when building capacity during global orthopaedic surgical outreach. The framework and its tiered system can be used to assess capacity and guide capacity-building efforts in LMICs. The developed blueprint can inform the operations of NGOs toward activities that focus on building capacity in order to ensure a measured and sustained impact.